Talking about Causing Events - Christopher A. Vogel; Alexis Wellwood; Rachel Dudley; J. Brendan Ritchie (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Questions about the nature of the relationship between language and extralinguistic cognition are old, but only recently has a new view emerged that allows for the systematic investigation of claims about linguistic structure, based on how it is understood or utilized outside of the language system. Our paper represents a case study for this interaction in the domain of event semantics. We adopt a transparency thesis about the relationship between linguistic structure and extralinguistic cognition, investigating whether different lexico-syntactic structures can differentially recruit the visual causal percept. A prominent analysis of causative verbs like move suggests reference to two distinct events and a causal relationship between them, whereas non-causative verbs like push do not so refer. In our study, we present English speakers with simple scenes that either do or do not support the perception of a causal link, and manipulate (between subjects) a one-sentence instruction for the evaluation of the scene. Preliminary results suggest that competent speakers of English are more likely to judge causative constructions than non-causative constructions as true of a scene where causal features are present in the scene. Implications for a new approach to the investigation of linguistic meanings and future directions are discussed.
Keywords: linguistic structure; language system; event semantics; transparency thesis; extralinguistic cognition